FINANCING INVESTMENTS DIRECTED TO THE REAL SECTOR OF THE ECONOMY IN DEVELOPED COUNTRIES (American Journal of Business Management, Economics and Banking, 2026)
This study examines the modern features of financing investments directed to the real sector of the economy in developed countries. The research analyzes the main sources of investment financing, including the role of bank loans, capital market instruments, venture capital, and private equity mechanisms. It also highlights the participation of the state in investment processes and its impact on economic efficiency. Based on the experience of developed countries, diversified and innovative approaches to financing the real sector are revealed. The results of the study contribute to the effective use of investment resources and ensuring economic growth.